Reproductive ecology and nest‐site selection of eastern wild turkeys translocated to east Texas - Jason L. Isabelle; Warren C. Conway; Christopher E. Comer; Gary E. Calkins; Jason B. Hardin (Wildlife Society Bulletin, 2016)
ABSTRACT Despite extensive restoration efforts in eastern Texas, USA, eastern wild turkey (Meleagris gallopavo silvestris; hereafter, turkey) densities remain considerably lower than in other southern states. To help understand this disparity, we studied reproductive ecology and nest‐site selection of turkeys translocated to 4 super‐stocked (≥70 turkeys released) sites in eastern Texas, 2007–2008. Median first nest‐initiation date (16 Apr) was similar between first and second year postrelease and release‐year nesting rates were highly variable (15–77% among sites) and lower than during year 2 at each site (69–92% among sites). Renesting rates and nest success rates across sites and years averaged 21% and 38%, respectively, and poult survival varied 0–51%, averaging 35% across sites and years. Nest sites had greater living woody vegetation, ground and screening cover, and ground cover height than random sites. Successful nests tended to have more (P > 0.05) shrubs, greater visual obstruction, and more and taller ground cover than unsuccessful nests. We recommend thinning pine (Pinus spp.) forests as young as possible, maintaining 0.5–1‐m‐tall vegetation to provide nesting cover, and managing these areas outside the nesting season (Apr–Jun) to minimize disturbance of nesting females. We recommend adults represent ≥50% of male turkeys during translocations to bolster nesting rates during the release year. Given sufficient nesting rates and survival, parameter estimates suggest adequate reproduction for turkey population establishment in eastern Texas. The presence of suitable nesting cover should be an important consideration when selecting future release sites. © 2016 The Wildlife Society.